Storage, utilization, and disposal of hematopoietic stem cell products in patients with multiple myeloma - Krummradt, Felix; Sauer, Sandra; Pavel, Petra; Klein, Eva-Maria; Schmitt, Anita; Kriegsmann, Mark; Jordan, Karin; Müller-Tidow, Carsten; Goldschmidt, Hartmut; Wuchter, Patrick; Kriegsmann, Katharina (Biology of blood and marrow transplantation, 2020)
High-dose chemotherapy (HD-CHT) and autologous blood stem cell transplantation (ABSCT) represent the standard of care in multiple myeloma (MM) for transplantation-eligible patients. Up to 3 HD-CHT/ABSCT treatments may be administered during the course of disease, including during late-onset relapse. Transplantation centers routinely collect more than 1 peripheral blood stem cell (PBSC) graft; however, subsequent HD-CHT/ABSCT treatments are often not performed, for various reasons. Currently, little is known about the actual utilization rate of stored PBSCs. The collection, storage, and disposal of PBSC products was analyzed in a large cohort of patients with MM (n = 1114) over a 12-year period with a minimum follow-up of 6 years. The final dataset analysis was performed in March 2019, which was set as the reference date. Based on institution-specific charges, the costs for PBSC collection, processing, and storage were estimated. The median number of sufficient PBSC transplantations per patient was 3 (range, 0 to 6), which were stored in a median of 3 (range, 1 to 11) cryopreserved bags (overall, n = 3644). A total of 95% of all patients (n = 1059) underwent at least 1 HD-CHT/ABSCT treatment. However, multiple ABSCTs were performed in 51% of the patients (n2/3 ABSCTs = 538), and only 14% of the patients underwent ABSCT 3 times (n3 ABSCTs = 149). Only a small proportion of collected PBSC bags (5%; n = 109) were used after being stored for longer than 5 years. Overall, 23% of the products (n = 830) were discarded, and 16% (n = 566) were kept in storage until the reference date. From a retrospective standpoint, the collected and discarded (definitively not used) or stored (potentially not used) cryostored PBSCs were associated with considerable costs for long-term cryostorage of approximately €1,600,000. We identified considerable discrepancies between the collection/storage and utilization of PBSCs. This is associated with significant efforts and costs on the one hand; on the other hand, disposal may raise legal and ethical questions. Therefore, we implemented comprehensive guidelines for the systematic reevaluation of stored PBSC grafts at our institution.